CONSUMER PROTECTION FOR FLIGHT DELAYS (FLIGHT DELAY) ON AIRLINES - Lastin, Juniant; Iqbal, Muhammad; nasution, anhar; saputra, jummaidi; Muksalmina, Muksalmina (Jurnal Ilmu Hukum Reusam, 2024)
The development of the times has changed the pattern of people's mobility, and aviation has become one of the popular modes of air transportation. However, flight delays that are sometimes experienced by passengers can cause both material and immaterial losses. Therefore, consumer protection is important to be guaranteed by the airline. The research method used is quantitative with a normative-empirical legal approach. Empirical research was conducted through interviews with the Directorate General of Civil Aviation to obtain primary data, while normative research was carried out by reviewing laws and regulations and related legal materials. The results of the study show that flight delays are a problem that is often experienced by passengers at SIM Aceh Besar Airport. From the results of the interviews and data collected, it was found that airlines do not always treat passengers well in dealing with delay situations, which should be in accordance with applicable regulations. Law Number 1 of 2009 concerning Aviation emphasizes the obligation of airlines to provide proper service to passengers, including in overcoming flight delays, and providing appropriate compensation if the delay is caused by the airline. In addition, the results of the study also revealed that Article 146 of the Law states that airlines are liable for losses suffered due to delays, unless caused by weather and operational technical factors. However, from interviews with passengers who experienced delays at SIM Aceh Besar Airport, it can be seen that they do not always provide compensation in accordance with the provisions, so they do not fulfill their obligations in providing consumer protection.